Pengaruh Kompensasi Dan Pengawasan Terhadap Disiplin Kerja Pegawai Pada Dinas Cipta Karya Dan Tata Ruang Kabupaten Kutai Kartanegara - Syahruddin Syahruddin (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2022)
Abstract :Office of Human Settlements and Spatial Kutai district is one of the local government agency that has the task of carrying out the authority of decentralization and deconcentration tasks in the field of Human Settlements, Spatial and Hygiene management, and Cemetery which is located street Wolter Monginsidi, Building ULP. Regent Office complex with the Head of Department Mr. H. Basrie Hasan ST., MT. the number of employees as many as 127 employees. The aim of this study was to apply the knowledge gained during this field and for the world to know and how much influence Compensation and Supervision influence the Work Discipline Employees At the Department of Human Settlement and Spatial Kutai district. Variable compensation and oversight together (simultaneously) be able to demonstrate its impact on employee discipline. The first hypothesis stated